Benzene Oxidation on Boron-Doped Diamond Electrode: Electrochemical-Impedance Study of Adsorption Effects - Yuri Pleskov; Marina Krotova; Valerii Elkin; Valentin Varnin; Irina Teremetskaya (International Journal of Electrochemistry)
Benzene oxidation at a boron-doped diamond anode in 0.5 M K2SO4 aqueous solution is studied by cyclic voltammetry and electrochemical impedance spectroscopy. It is shown by measurements of differential capacitance and anodic current that in the ideal-polarizability potential region benzene either is not adsorbed at the diamond electrode or the benzene adsorption does not affect its capacitance. At more positive potentials, the adsorption of some intermediate of the benzene oxidation occurs at the electrode. The intermediate partially blocks the electrode surface and lowers the anodic current. The very fact of the electrode surface blocking is reflected in the complex-plane presentation of the impedance-potential plots.